New records of plants from the mountains of northern Mexico - Spellenberg, Richard; Lebgue, Toutcha; Corral-Diaz, Rafael; Bacon, Jeffrey (Instituto de Ecología, A.C., 1995)
Twenty new records in 13 families from the mountains of northern Mexico are reported. Most were derived from our floristic studies in the Parque Nacional de la Cascada de Basaseachic, Chihuahua, during the last seven years.